Dopamine Transporter Imaging Using (99m)Tc-TRODAT-1 SPECT in Parkinson’s Disease - Bor-Seng-Shu, Edson (International Scientific Literature, Inc., 2014)
BACKGROUND: Although the decrease in striatal dopamine transporter (DAT) density has been described in North American, European, and Asian Parkinson’s disease (PD) patients, studies on this issue are required in the rest of the world. This study examined the diagnostic utility of DAT imaging in Brazilian PD patients. MATERIAL/METHODS: Twenty PD patients (13 males, 7 females, median age: 62 years, median age at disease onset: 56 years, median disease duration: 5 years, and median UPDRS-III score: 29) and 9 age- and sex-matched healthy subjects underwent single-photon emission computerized tomography (SPECT) using (99m)Tc-TRODAT-1. RESULTS: PD patients showed a significant decrease in the striatum, caudate nucleus, and putamen DAT densities compared with data from healthy subjects. Striatal (99m)Tc-TRODAT-1 bindings had the highest diagnostic accuracy compared to those estimates from caudate nucleus and putamen. For the diagnosis of PD, a striatal (99m)Tc-TRODAT-1 binding cut-off value of 0.90 was associated with a sensitivity of 100% and a specificity of 89%. There was no significant difference between striatal (99m)Tc-TRODAT-1 binding values provided by different readers, contrary to (99m)Tc-TRODAT-1 binding estimates in the caudate nucleus. CONCLUSIONS: Striatal DAT imaging using (99m)Tc-TRODAT-1 can be considered a marker for differentiating PD patients from healthy individuals, with a good interobserver reproducibility.